Correlation of Guaiacol Production With Presence and Expression of the Guaiacol Biosynthetic Gene Cluster in Alicyclobacillus Spp - Rui Cai; Yanhui Li; Qi Wang; Hong Guo; Yuxiang Zhang; Yahong Yuan; Qinglin Sheng; Zhouli Wang; Tianli Yue (eFood)
ABSTRACT The whole genome sequences of A. dauci DSM 28700, A. fastidiosus KKP 3000 (guaiacol producers), and A. fastidiosus DSM 17978 (non‐guaiacol producer) were firstly determined. Then, the presence of the guaiacol biosynthetic gene cluster in genome sequences of 7 guaiacol‐producing and 16 non‐guaiacol producing Alicyclobacillus strains was explored. Of the 7 Alicyclobacillus guaiacol producers investigated, a complete guaiacol biosynthetic gene cluster was found in A. fastidiosus K3000, A. acidiphilus NBRC 100859, A. dauci DSM 28700, A. suci VF‐FSL‐W10‐0049 and FSL‐W10‐0048; only guaB, guaC, guaD, and guaE genes were found in A. herbarius DSM 13609, and guaA, guaB, guaC, guaD, and guaE genes were found in A. hesperidum subsp. aegles DSM 11985. There was no complete guaiacol gene cluster present in the tested 16 Alicyclobacillus non‐guaiacol producers. The expression kinetics of genes in the guaiacol biosynthetic gene cluster under the conditions of producing and not producing guaiacol indicated that the expression of the 6 genes was closely related to the production of guaiacol in A. acidoterrestris. These findings will facilitate a deeper understanding of guaiacol production in Alicyclobacillus spp., which will contribute to develop effective control methods to minimize Alicyclobacillus‐related spoilage in the fruit juice industry.